Improving Elementary Students’ Listening Comprehension and Learning Motivation through Classroom Action Research Using Puppet Show Media - Herwin Anggraini; Supartinah; Muh Saidil Ikhwan (Papanda Publisher, 2026)
This study examines the effectiveness of puppet show media in improving learning motivation and listening comprehension in Indonesian language listening instruction among second-grade elementary school students through Classroom Action Research (CAR). The research was conducted with 23 students of class II A at a public elementary school and implemented two action cycles, each consisting of planning, action, observation, and reflection stages. Data were collected using motivation questionnaires, listening comprehension tests, classroom observations, and field notes, and were analyzed using descriptive statistics and qualitative analysis. The results demonstrate a consistent improvement in both variables across cycles. Students’ learning motivation, measured as the average questionnaire score converted into a percentage of the maximum possible score, increased from 49.2% in the pre-cycle to 56.2% in Cycle I and reached 78.9% in Cycle II. Meanwhile, listening comprehension achievement, measured by the percentage of students attaining the minimum mastery criterion, rose from 34.78% in the pre-cycle to 52.2% in Cycle I and 95.7% in Cycle II. These findings indicate that puppet show media provide engaging multimodal learning experiences by integrating visual character representation, puppet movement, teacher narration, voice intonation, dialogue, and interactive questioning activities, which effectively enhance students’ motivation and listening comprehension. This study highlights the potential of CAR as a reflective approach to improving instructional practices in elementary classrooms.